2011
DOI: 10.1212/wnl.0b013e31820c3052
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying excessive mirror overflow in children with attention-deficit/hyperactivity disorder

Abstract: The quantitative overflow measures used in this study support past qualitative findings that motor overflow persists to a greater degree in children with ADHD than in age-matched TD peers. The quantitative findings further suggest that persistence of mirror overflow is more prominent during task execution of the nondominant hand and reveal gender-based differences in developmental neural systems critical to motor control. These quantitative measures will assist future physiologic investigation of the brain bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 27 publications
(22 reference statements)
9
66
0
2
Order By: Relevance
“…This could indicate a stronger propagation of TMS-evoked activity in the motor system of children with ADHD to the supplementary motor area or even to the contralateral motor cortex. In this respect, more mirror movements have been described in children with ADHD and may point towards deficits in transcallosal inhibition in ADHD (Macneil et al, 2011). Though MEP data were not available for all subjects, the results showed a clear dissociation between TMS-evoked N100 and MEP amplitudes.…”
Section: Methodological Issuesmentioning
confidence: 76%
“…This could indicate a stronger propagation of TMS-evoked activity in the motor system of children with ADHD to the supplementary motor area or even to the contralateral motor cortex. In this respect, more mirror movements have been described in children with ADHD and may point towards deficits in transcallosal inhibition in ADHD (Macneil et al, 2011). Though MEP data were not available for all subjects, the results showed a clear dissociation between TMS-evoked N100 and MEP amplitudes.…”
Section: Methodological Issuesmentioning
confidence: 76%
“…Even as adults we may experience occasional mirror overflow (e.g., activity in the lips or hands), as when focusing intently on a precise task. Elevated overflow is revealed consistently in children with ADHD across a range of studies using a variety of methodologies to quantify motor overflow movements (Mostofsky et al, 2003;Cole et al, 2008;MacNeil et al, 2011). Furthermore, among children with ADHD, increased levels of motor overflow correlate with measures of impaired cognitive control (Mostofsky et al, 2003).…”
Section: Overt Motor Behavior In Adhdmentioning
confidence: 98%
“…Studies consistently reveal extremely high rates (50% and above) of comorbid Developmental Coordination Disorder (DCD) in children with ADHD (Kadesjö and Gillberg, 2001), in particular, impairments in motor inhibition and selection correlate with the deficits in attention and cognitive control that define the disorder MacNeil et al, 2011), and measures of automatic and intentional motor inhibition are likewise correlated (Mostofsky et al, 2003). In studies of specific overt motor signs, investigators have consistently found children with ADHD show excessive motor overflow (Denckla and Rudel, 1978;Szatmari and Taylor, 1984;Waber et al, 1985;Mostofsky et al, 2003;Cole et al, 2008;MacNeil et al, 2011), and impaired motor response control (Mostofsky et al, 2003;Mahone et al, 2006), as well as general findings of impaired motor coordination (Denckla and Rudel, 1978;Piek et al, 1999;Kadesjö and Gillberg, 2001;Mostofsky et al, 2003;Cole et al, 2008). Children with ADHD also demonstrate motor impersistence reflective of broader impairments in maintaining on-task behavior (Mahone et al, 2006).…”
Section: Overt Motor Behavior In Adhdmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually motor overflow is evaluated through asking subjects to perform such goal-oriented tasks as sequential finger-tapping with one hand while observing for extraneous or mirror movements in other non-tapping body parts. Several studies indicate that these overflow movements can be considered predictive markers for ADHD (Barkley, 1997;Macneil et al, 2011;Mostofsky, Newschaffer, & Denckla, 2003). As mentioned above, problems with sensorimotor skills, coordination, and movement control are primarily considered to be expressions of impaired cognitive processes necessary for planning and performing goal-directed tasks-that is, so-called executive function and selfregulation.…”
Section: Overflow Movements and Exploring What Happens To Youmentioning
confidence: 99%